Μελέτη και σχεδιασμός ηλεκτρικού αυτοκινήτου πόλης - Μανίκας, Γεώργιος (2021)
The present thesis investigates the problematic situations, arising nowadays in an urban environment, due to the presence of the car. Three designing proposals of mini electric vehicles, destined for urban use, are suggested in order to resolve the existing problems. More precisely, the investigation focuses on and analyses the problematic situations a city resident faces every day because of the use of the car, like the pollution of the environment, health aggravation, as well as the difficulties one encounters while driving around the city. The investigation continues with the study of electric mobility, citing its advantages and the reasons it could possibly be the solution to the urban transportation problems. With the ultimate aim of composing the design specifications of this project, significant city cars, electric or not, are mentioned throughout the thesis presenting the advantages of each one of them. Subsequently, a research is being held around the issue of car design and fields that will help to the final design, are being studied in detail. The thesis is completed with the final designing proposals and the arising conclusions.